Saklikent Canyon (Fethiye- Turkey) - Sengun, M. Taner (Elsevier Science Bv, 2011)
In the globalizing world, people who want to escape from the impact of urbanization prefer natural beauties remarkable with its geomorphological characteristics. Curiosity to discover is the motivation for this. In this study, formation and geomorphological characteristics of the Saklikent Canyon has been analyzed, its tourism potential introduced. The natural environmental planning needed to be realized in the canyon, precautions to be taken in the case of risks such as flood, and actions to be taken are offered. This Canyon is located in the southwestern part of Turkey, 40 km from the district of Fethiye in the city of Mu la. It is not popular among domestic tourists. The length of the Canyon is approximately 18 km. Karacay (Kocacay) as one of the tributaries of E en brook is effective in the formation of this canyon. The altitude of canyon slopes varies between 100 to 350 meters. Gradient of the slopes reaches to 90 in some locations. The latitude in the canyon reaches to 4-5 meter while in some locations it is narrowing in such a way that one cannot open its arms. Walking in the canyon is difficult related to the river burnishing the ground of the canyon. In terms of formation, the canyon has an antecedent characteristic. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The 2nd International Geography Symposium-Mediterranean Environment
2nd International Geography Symposium-Mediterranean Environment -- JUN 02-05, 2010 -- Antalya, TURKEY
Keywords: Fethiye; Saklikent Canyon; geomorphology